Analysis of the Nature Marriage in the Perspective of Islamic Family Law - Norcahyono, Norcahyono; Koto, Alaiddin; Hanafi, Muhammad; Mulyani, Ridha; Safitri, Noraya (Jurnal Elsyakhshi, 2024)
Marriage is a strong bond that creates peace, happiness, and love (harmony). However, the reality is that disharmony is currently the reason for divorce. The couple's lack of knowledge about the nature and purpose of marriage is the main factor in this disharmony. According to Islamic family law, this research aims to analyze the nature of marriage and the responsibilities of husband and wife in marriage. This research uses a qualitative method with a descriptive-analytical approach. Data sources were obtained from Islamic legal sources such as the Alquran, Hadith, translations of fiqh books, Islamic legal literature, and journals. The data collection technique in this research is documentation of these sources. The main source of Islamic family law discusses the nature of marriage in guiding muslim families to build and care for the family so that it becomes an ideal and happy family. The results of this research show that: i) the nature of marriage from the perspective of Islamic family law ii) the five responsibilities of the husband in the family and the six responsibilities of the wife in the muslim family are by the Alquran and Hadith.